2014
DOI: 10.1093/icesjms/fsu054
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of bottom trawling and a storm event on soft-bottom benthos in the eastern Bering Sea

Abstract: A Before–After Control–Impact (BACI) experiment was conducted to investigate the effects of a commercial bottom trawl on benthic invertebrates in a sandy and previously untrawled area of the eastern Bering Sea. Six pairs of experimental and control corridors were sampled with a research trawl before and after four consecutive tows with the commercial otter trawl. A major storm event occurred during the experiment, and it was possible to differentiate its effect from that of the trawling using the BACI model. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…For these species, recovery largely depends on recruitment, settlement and growth in impacted areas and the extent of substrate modification following the fishing event. For example, many sessile invertebrates such as anemones, tunicates and soft corals in sandy disturbed areas of the Bering Sea depend on empty shells for attachment, and trawling can bury these shells and hamper their recovery (McConnaughey & Syrjala, ).…”
Section: Discussionmentioning
confidence: 99%
“…For these species, recovery largely depends on recruitment, settlement and growth in impacted areas and the extent of substrate modification following the fishing event. For example, many sessile invertebrates such as anemones, tunicates and soft corals in sandy disturbed areas of the Bering Sea depend on empty shells for attachment, and trawling can bury these shells and hamper their recovery (McConnaughey & Syrjala, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sciberras et al . ; McConnaughey and Syrjala ). Understanding which combination of habitat variables predicts recovery would facilitate the development of broad scale predictive maps of habitat sensitivity that could be used for management purposes (see Hiddink et al .…”
Section: Discussionmentioning
confidence: 97%
“…the winter when many benthic biota are senescent (Van Denderen et al 2015). McConnaughey and Syrjala (2014) suggested that the benthic habitat in their Bering Sea study area is affected more by natural storm events than trawl disturbance. If we are to assess change in seabed habitats and their biota in relation to fishing this implies that we understand the status of those habitats prior to the commencement of fishing.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations